تقويم أهداف برنامج الاقتصاد المنزلي في كلية التربية للبنات- جامعة بغداد من وجهة نظر هيئة التدريس وطالبات المرحلة الرابعة - بستان، إسراء كامل (Kulliyah of Education, International Islamic University Malaysia, 2017)
One of the most notable features of the current era is the wide use of science and technology in our life. Hence, creative and scientific thinking has become one of the basic requirements of life. This has prompted many countries to give high importance to education, because it can contribute to the progress of nations and their development by keeping abreast of technological developments in various spheres of life. Continuous evaluation of educational goals contributes to the development and reform of curricula and meet the ambitions of the community thereby raising the quality of the educational process. This will also help to give a clear picture for decision makers about the real situation within the education system. Therefore, the current research aims to evaluate the objectives of the Home Economics program in the department of Home Economics under the college of education at Baghdad University based on the perspectives of 40 lecturers' and 120 fourth year students studying Home Economics. A questionnaire was administered to the participants and then the (Smart PLS) program was used to analyse the data. The researcher concluded that there are deficiencies in some of the objectives of the home economics program, especially in terms of the consistency of the objectives with regard to the nature of the society, current context, and level of awareness; the relevance, balance, integration, and comprehensiveness of the program's objectives; in addition to their breadth and diversity. As a result, the study recommended that there is a need to address these limitations through re-planning the home economics program in the light of modern changes and current life issues within the Iraqi society, especially the economic crisis experienced by the Iraqis. There is a need to enrich the content of the home economics program and to add topics that are beneficial for students to help them achieve balanced personal development, through the assistance of specialized educational experts and qualified faculty members.